CRISPR/Cas9-Mediated Deletion of CTG Expansions Recovers Normal Phenotype in Myogenic Cells Derived from Myotonic Dystrophy 1 Patients - Claudia Provenzano; Marisa Cappella; Rea Valaperta; Rosanna Cardani; Giovanni Meola; Fabio Martelli; Beatrice Cardinali; Germana Falcone (Elsevier, 2017)
Myotonic dystrophy type 1 (DM1) is the most common adult-onset muscular dystrophy, characterized by progressive myopathy, myotonia, and multi-organ involvement. This dystrophy is an inherited autosomal dominant disease caused by a (CTG)n expansion within the 3' untranslated region of the DMPK gene. Expression of the mutated gene results in production of toxic transcripts that aggregate as nuclear foci and sequester RNA-binding proteins, resulting in mis-splicing of several transcripts, defective translation, and microRNA dysregulation. No effective therapy is yet available for treatment of the disease. In this study, myogenic cell models were generated from myotonic dystrophy patient-derived fibroblasts. These cells exhibit typical disease-associated ribonuclear aggregates, containing CUG repeats and muscleblind-like 1 protein, and alternative splicing alterations. We exploited these cell models to develop new gene therapy strategies aimed at eliminating the toxic mutant repeats. Using the CRISPR/Cas9 gene-editing system, the repeat expansions were removed, therefore preventing nuclear foci formation and splicing alterations. Compared with the previously reported strategies of inhibition/degradation of CUG expanded transcripts by various techniques, the advantage of this approach is that affected cells can be permanently reverted to a normal phenotype.